The relationship between resilience and psychological characteristics of paramedicine students. (September 2022) - Mason, Rod; Roodenburg, John; Williams, Brett
Abstract: Background: Paramedics' continued exposure to occupational stressors can have a detrimental effect on their psychological well-being. Resilience can provide for better coping. Understanding individual differences provides explanations why some individuals thrive while others are more at risk. Aim: To explore the effect of Personality according to the Big-Five, Ways of Thinking and Occupational Preference according to Holland's RIASEC Model, on resilience. Method: Using a quantitative cross-sectional design, The Big-Five Inventory, Ways of Thinking, Brief RIASEC Marker Scales and Connor Davidson CD-RISC were administered. Results: Standard Multiple Regression showed that resilience is more likely to be seen in those who score high in Conscientiousness and low in Neuroticism. Modelling also showed that resilience is more likely to be seen in those who score high in Surgency ( β  = 0.364, p = .001) followed by the Freethinker ( β  = 0.312, p = .001), Scientific ( β  = 0.112, p = .027) and Controlled ( β  = 0.105, p = .040) ways of thinking. Although the RIASEC model was not a strong predictor of resilience, the Social ( β  = 0.252, p = .001) and Investigative ( β  = 0.153, p = .020) factors were highlighted as contributing towards a paramedic's resilience. Conclusion: The paramedicine students that participated in this study report higher levels of some of the personality traits inherently protective in facilitating resilience.